Dimensions of Impulsivity in Gambling Disorder - Mestre-Bach, Gemma; Steward, Trevor; Granero, Roser; Fernández-Aranda, Fernando; Mena-Moreno, Teresa; Vintró-Alcaraz, Cristina; Lozano-Madrid, María; Menchón, José M.; Potenza, Marc N.; Jiménez-Murcia, Susana (Scientific Reports, 2020)
Impulsivity is a multidimensional construct. Although gambling disorder (GD) has been associated with high impulsivity, impulsivity across multiple domains has not been thoroughly investigated in this population. We first aimed to examine whether associations between three facets of impulsivity (response impulsivity, choice impulsivity and impulsive tendency) varied between GD patients and healthy controls (HC). We next aimed to evaluate relationships between these three types of impulsivity, as proposed by theoretical models of impulsivity, and their associations with GD severity. The sample included 97 treatment-seeking adult men with GD, diagnosed according to DSM-5 criteria, and 32 male HCs recruited from the general population. Greater impulsivity in all three domains was found in men with GD in comparison to men without GD. Associations between impulsivity facets were found in both groups, with response impulsivity being the only domain associated with GD severity. Our findings confirm that multiple domains of impulsivity are relevant in GD. Future studies should examine the extent to which treatments aimed at targeting specific aspects of impulsivity improve outcomes.
Keywords: Scopus; JCR